Hierarchical Porous Carbon-PLLA and PLGA Hybrid Nanoparticles for Intranasal Delivery of Galantamine for Alzheimer's Disease Therapy - Stavroula G. Nanaki; Konstantinos Spyrou; Chryssa Bekiari; Pelagia Veneti; Turki N. Baroud; Niki Karouta; Ioannis Grivas; Georgios C. Papadopoulos; Dimitrios Gournis; Dimitrios N. Bikiaris (MDPI AG, 2020)
In the present study, poly(l-lactic acid) (PLLA) and poly(lactide-co-glycolide) (PLGA) hybrid nanoparticles were developed for intranasal delivery of galantamine, a drug used in severe to moderate cases of Alzheimer’s disease. Galantamine (GAL) was adsorbed first in hierarchical porous carbon (HPC). Formulations were characterized by FT-IR, which showed hydrogen bond formation between GAL and HPC. Furthermore, GAL became amorphous after adsorption, as confirmed by XRD and differential scanning calorimetry (DSC) studies. GAL was quantified to be 21.5% w/w by TGA study. Adsorbed GAL was nanoencapsulated in PLLA and PLGA, and prepared nanoparticles were characterized by several techniques. Their sizes varied between 182 and 394 nm, with an exception that was observed in nanoparticles that were prepared by PLLA and adsorbed GAL that was found to be 1302 nm in size. DSC thermographs showed that GAL was present in its crystalline state in nanoparticles before its adsorption to HPC, while it remained in its amorphous phase after its adsorption in the prepared nanoparticles. It was found that the polymers controlled the release of GAL both when it was encapsulated alone and when it was adsorbed on HPC. Lastly, PLGA hybrid nanoparticles were intranasally-administered in healthy, adult, male Wistar rats. Administration led to successful delivery to the hippocampus, the brain area that is primarily and severely harmed in Alzheimer’s disease, just a few hours after a single dose.